Job Demands and Resources, Mindfulness, and Burnout Among Delivery Drivers in China - Zhang, Congcong; Cheung, Shannon P.; Huang, Chienchung (Frontiers in Psychology, 2022)
The food and package delivery workforce in China has grown substantially in the past decade. However, delivery drivers face volatile and stressful work conditions, which can give rise to high turnover and burnout. Past research has indicated that job demands and resources (JD-R) significantly predict burnout. Scholars have also found evidence that mindfulness may be a protective factor against negative outcomes like burnout. Using data collected from 240 food and package delivery drivers in Beijing, China, we examined the effects of JD-R on burnout and whether these relations were moderated by mindfulness. Estimates produced by regression analyses indicated that job demands (JD) have significantly positive effects on burnout (Beta=0.33), while job resources (JR) have a significant negative effect on burnout (Beta=-0.32). Mindfulness significantly moderated the effects of JD and JR on burnout (Beta=-1.64 and -1.30, respectively). Results suggest that mindfulness is a protective factor for delivery drivers. Practice and policy implications are discussed.